BIOMECHANICAL DIFFERENCES BETWEEN CASES WITH CECS AND ASYMPTOMATIC CONTROLS DURING WALKING AND MARCHING. Issue 22 (1st November 2016) - Roberts, A; Roscoe, D; Hulse, D; Bennett, A; Dixon, S
Abstract : No primary research has been carried out to investigate the predisposing biomechanical and anthropometric factors for chronic exertional compartment syndrome. The aim of this study was to investigate the kinematic and kinetic differences in cases with chronic exertional compartment syndrome and controls. 20 males with symptoms of chronic exertional compartment syndrome of the anterior compartment and 20 male asymptomatic controls were studied. Anthropometry and three-dimensional kinematics and kinetics were compared during walking and marching. Bootstrapped t-tests were carried out on each individual normalised time point to identify regions within the gait cycle that were significantly different. Cases were shorter in stature and took a relatively longer stride in relation to leg length than controls. There were no differences in weight or height-to-leg length ratio. Kinematic differences were only identified at the ankle. Cases demonstrated increased ankle plantarflexion from mid-stance to toe-off. Cases also demonstrated less ankle inversion at the end of stance and early swing phases which coincided with the generation of lower ankle inversion moments. The anthropometric and biomechanical differences demonstrated provide a plausible mechanism for the development of chronic exertional compartment syndrome in this population. Shorter stature in combination with a relatively longer stride length may result in an increased demand on tibialis anterior during ambulation. The speed at which humans begin to transition to running is dependent on stature and is close to the marching speed in this study. Tibialis anterior is reported to be a key determinant of this speed. Many participants reported having previously experienced the urge to transition to a run in order to alleviate their pain. The results of this study, together with clinical insights and published research suggest that the suppression of the walk-to-run stimulus during military group marches may play a significant role in the development of chronic exertional compartment syndrome within a military population. The differences in joint angles and moments also indicate an impairment of the effectiveness of tibialis anterior. It is unclear whether this is a cause or consequence of chronic exertional compartment syndrome.